2009
DOI: 10.1002/jctb.2251
|View full text |Cite
|
Sign up to set email alerts
|

Separation and recovery of cellulose and lignin using ionic liquids: a process for recovery from paper‐based waste

Abstract: BACKGROUND: The production of paper makes use of cellulose and lignin as a raw material, and almost all cellulose and lignin production comes from raw wood materials, contributing to deforestation and resulting in potential environmental harm. It is therefore beneficial to develop technologies for cellulose and lignin recovery for re-use and sustainability of resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 36 publications
2
71
1
Order By: Relevance
“…5. The lignin molecule contains various functional groups such as O-H, C-H, C-O, etc., for which bond vibrations are shown in Table 3 [25]. Bamboo lignin contains high proportion of syringyl residues which can be observed by an intense single peak at 832 cm −1 and more intense peaks at 1,128 and 1,320 cm −1 in the FTIR spectrum B [26].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…5. The lignin molecule contains various functional groups such as O-H, C-H, C-O, etc., for which bond vibrations are shown in Table 3 [25]. Bamboo lignin contains high proportion of syringyl residues which can be observed by an intense single peak at 832 cm −1 and more intense peaks at 1,128 and 1,320 cm −1 in the FTIR spectrum B [26].…”
Section: Resultsmentioning
confidence: 98%
“…This absence of lignin characteristic peaks confirmed the delignification of the regenerated biomass. The peaks which appear at around 1,328, 1,159, 1,037, 1,056, and 896 cm −1 are mainly attributed to the carbohydrates which are present in both spectra [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…The very high solvating properties of RTILs have been exploited in the dissolution of cellulose (Kosan et al, 2008;Swatloski et al, 2002), lignin (Lateef et al, 2009), and even whole wood (Fort et al, 2007;Honglu and Tiejun, 2006;Kilpelainen et al, 2007), and such solvating power has led to a number of studies where RTILs have been considered for biomass pretreatment. Herein, we provide an overview of recent scientific and technological advances on the use of RTILs in lignocellulosic biomass pretreatment, including their critical unique solvating power.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of ILs with terminal hydroxyl groups of lignin, resulting disruption of lignin-cellulose network of biomass, thus increase the release of the regenerated lignin. Lateef et al (2009) also reported the disruption of the internal network within lignin molecule would affect the dissolution of lignin. Although, chloride anion showed good lignin extraction, but it has high liquid viscosity and high melting temperature compared to acetate anion.…”
Section: Effect Of the Cations And Anions In The Ionic Liquids On Thementioning
confidence: 99%